Gains from Crime Do metal thieves respond to raising prices of non-ferrous metals? - Brabenec, Tomáš; Montag, Josef; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
This paper estimates the elasticity of supply-of-offences with respect to the gains from crime. Previous studies have uncovered little evidence because standardly used proxies for gains from crime such as average income suffer substantial problems. They are slightly variable and/or may represent the opportunity cost of crime at the same time. This paper uses higly fluctuating world prices on non-ferrous metals as proxy for the gains from crime. Using monthly data about metal thefts in the Czech Republic for years 2003-2009 estimates elasticity of supply-of-offences. The estimated elasticity with respect to copper price are around 0,6.
Vedoucí práce: Josef Montag
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses